IMPLEMENTATION OF E-BOOK-BASED TEACHING MATERIALS FOR MAKEUP LEARNING: INDONESIA EXPERIENCE - Handayani Desi; Sofyan Herminarto (Borys Grinchenko Kyiv Metropolitan University, 2022)
This article aims to uncover the implementation of e-book-based teaching materials for makeup learning. The method used in this article is the literature review. Based on the study of literature it can be concluded that among the teaching materials e-book is important to pay attention to the constituent components, namely. (a) Display of e-book teaching materials, including book cover design, shape, size, and image. (b) The content of the e-book teaching materials, including the composition of the text, the standard rules of book preparation (aspects of material completeness, language, and usefulness), and dictionaries or glossaries. The learning of the history of Makeup is very important to be mastered by students because the learning of the history of makeup trains students in practicing their knowledge and for the provision of students after graduating from college so that students majoring in skin beauty can open a business in the field of bridal makeup. Related to this, students must be able to master the history of makeup well. On the other hand, students still have a lot of difficulty in mastering the concept of learning the history of makeup and still lack references obtained by students to increase their knowledge. The use of learning media is considered as one of the most appropriate solutions in presenting bridal makeup materials in learning. In addition, the study of the history of makeup is one of the learnings that must students in understanding the concepts contained in it, such as the wedding ceremony, wearing clothes and accessories, and how to apply makeup of the bride.